Genomic Microarray in Intellectual Disability: The Usefulness of Existing Systems in the Interpretation of Copy Number Variation - Ben Khelifa, Hela; Soyah, Najla; Labalme, Audrey; Guilbert, Helene; Sanlaville, Damien; Saad, Ali; Mougou-Zerelli, Soumaya (Journal of Pediatric Genetics, 2017)
Whole genome array technology is an essential tool for the detection of a large number of copy number variants (CNVs) in patients with ID and/or multiple congenital anomalies. However, the clinical significance of some microimbalances is not known. In this article, we succeeded to detect seven new variations of unknown significance (dup12p13.33, dup2p16.3, dupXq13.2, del12q24.33, dup16p13.11, trip4q22.1, and dup9p21.3), one CNV classified as known pathogenic syndrome (del22q13.31-q33), and one CNV classified as potentially pathogenic (del11q24.3). We emphasize the role of comparative genomic hybridization arrays in the investigation of intellectual disability and evaluate the usefulness of existing systems in the interpretation of CNVs.
Keywords: intellectual disability; comparative genomic hybridization array; copy number variants; qPCR